2013
DOI: 10.1017/s0033291713002249
|View full text |Cite
|
Sign up to set email alerts
|

Guided Internet-delivered cognitive behavioural treatment for insomnia: a randomized trial

Abstract: Background. Insomnia is a prevalent problem with a high burden of disease (e.g. reduced quality of life, reduced work capacity) and a high co-morbidity with other mental and somatic disorders. Cognitive behavioural therapy (CBT) is effective in the treatment of insomnia but is seldom offered. CBT delivered through the Internet might be a more accessible alternative. In this study we examined the effectiveness of a guided Internet-delivered CBT for adults with insomnia using a randomized controlled trial (RCT).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 50 publications
3
80
2
1
Order By: Relevance
“…This is additionally supported by the low intervention-dropout rate (5%) and low study attrition. Intervention and study adherence was generally higher than with a traditional group face-to-face training (ie, 23) or guided and un-guided internet-based interventions targeting stress or insomnia (29,(64)(65). Our high adherence rates may be due to the guidance in the training in combination with the personal contact in the diagnostic interviews.…”
Section: Discussionmentioning
confidence: 74%
“…This is additionally supported by the low intervention-dropout rate (5%) and low study attrition. Intervention and study adherence was generally higher than with a traditional group face-to-face training (ie, 23) or guided and un-guided internet-based interventions targeting stress or insomnia (29,(64)(65). Our high adherence rates may be due to the guidance in the training in combination with the personal contact in the diagnostic interviews.…”
Section: Discussionmentioning
confidence: 74%
“…anxiety disorders, depression, body dissatisfaction, sexual dysfunction) have been meta-analytically shown to result in medium to large treatment effects that are comparable to those of their face-to-face equivalents (Andersson, Cuijpers, Carlbring, Riper, & Hedman, 2014). e-mental health interventions are usually based on CBT and they have been shown to be effective in reducing symptoms of common mental disorders such as PTSD (Kuester, Niemeyer, & Knaevelsrud, 2016; Sijbrandij, Kunovski, & Cuijpers, 2016), depression (Andrews, Cuijpers, Craske, McEvoy, & Titov, 2010), phobia (Andrews et al, 2010), panic disorder (Carlbring et al, 2006), and insomnia (van Straten et al, 2014), among others.…”
Section: Scaling-up With E-mental Health Interventionsmentioning
confidence: 99%
“…Short periods of sleep also appear to be a risk factor for hypertension (Fernandez-Mendoza et al, 2012;Vgontzas, Liao, Bixler, Chrousos, & Vela-Bueno, 2009) and type 2 diabetes mellitus. More seriously, sleep problems are related to an increased risk of alcohol and substance use, suicide, and mortality (Taylor, Lichstein, & Durrence, 2003;van Straten et al, 2014). Additional research has revealed that insomnia is associated with impaired quality of life and functioning (Kyle, Morgan, & Espie, 2010) and incurs great societal and financial costs.…”
Section: Comorbid Physical and Psychological Conditionsmentioning
confidence: 99%
“…As is apparent, there are many well-documented concerns and negative effects of sleep medication use among older adults. In general, sleep medications increase daytime drowsiness and the risk of falls and traffic accidents, are associated with anterograde amnesia, and may lead to tolerance, abuse, adverse physical and psychological withdrawals, and insomnia symptom rebound problems, in which insomnia symptoms reappear (sometimes worse than when they first occurred) following the discontinuation of sleep medications (Holbrook, Crowther, Lotter, Cheng, & King, 2000;McCall, 2005;Taylor & Weiss, 2009;van Straten et al, 2014). Further, research examining the relationship between the prevalence of delirium in 374 hospitals across the U.S. and sedative medication use found a significant correlation between the use of diphenhydramine and short-acting benzodiazepines and risk of developing delirium (Rothberg, Herzig, Pekow, Avrunin, Lagu, & Lindenauer, 2013).…”
Section: Insomnia Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation